Investigating Students’ Perceptions of Motivating Factors of Online Class Discussions - Lee, Joohi; Martin, Lesisa (International Review of Research in Open and Distributed Learning, 2017)
One of the goals of teacher education is to prepare our citizens to communicate in a variety of ways. In our present society, communication using digital media has become essential. Although online discussions are a common component of many online courses, engaging students in online discussions has been a challenge. This study queried 86 educators in a math/science teacher education graduate program to examine their perceptions on the factors that motivate them to participate in online discussions.The results revealed a pragmatic outlook on online education. In terms of intrinsic versus extrinsic motivation, the participants’ main motivation to participate in online class discussions was extrinsic (85.88%), specifically so that they could earn an acceptable participation grade. With regards to discussion grouping formats, they preferred small group discussions (81%) which could facilitate their ability to develop rapport with a small group of fellow classmates over whole class discussion (38.83%). With respect to discussion facilitation, they focused on the practical need to have the instructor to answer their questions about course assignments (67.06%) over online open discussion without a given topic (35.72%). Next, when asked about discussion question types based on Bloom’s taxonomy, their strongest preference reflected a desire for application (89.54%) questions which would facilitate their ability to use theories discussed in class in their daily work as educators. Through collaboration with twenty-first-century learners, online education can use data-driven decision making to help transform online discussion from being the least desirable component of online courses to a more relevant, instructional medium.